Experimental Evaluation Of Impact Based Flexible Piezoelectric P (VDF-TrFE) Thick-Film - Chow, Khoon Keat; Kok, Swee Leong; Lau, Kok Tee (Centre For Advanced Research On Energy (UTeM), 2017)
This paper discusses on the evaluation of an impact based energy harvesting material using poly(vinylidene fluoride) trifluoroethylene P(VDFTrFE) in the form of thick film on a flexible substrate. When an impact force from free-fall of 0.2N was applied to the film, as an energy harvester, a maximum peak-to-peak voltage of about 3.0V was generated which derived a maximum output power of 4.36 μW at an external load of 1kΩ.